Introgression Breeding in Cowpea [Vigna unguiculata (L.) Walp.] - Boukar, Ousmane (Front Plant Sci, 2020)
The narrow base of genetic diversity characteristic of cowpea can be attributed to it being self-pollinating, evolving from narrow wild germplasm and exhibiting very limited gene flow between wild and cultivated types. Backcrossing to introduce simply inherited desirable traits and utilization of improved breeding lines and varieties as parents in crossing programs further narrowed the genetic base of cowpea varieties. In most cowpea breeding programs, genes for resistance and market traits were pyramided into lines characterized by high levels of acceptance to farmers and consumers. Besides predisposing widely distributed improved varieties to genetic vulnerability, a narrow base of genetic variation may be contributing to the plateauing in cowpea grain yield, which compromises genetic gains. Cross compatible wild relatives have not been used in variety development because breeders shy away from them due to their tiny seed size, unattractive seed coat color and texture, pod shattering, and susceptibility to viruses. A number of wild cowpea relatives, both within and outside section Catiang of Vigna species, have been evaluated for their reaction to cowpea insect pests and diseases. Vigna vexillata lines were resistant to the legume pod borer (Maruca vitrata), the cowpea weevil (Callosobruchus maculatus), and Striga gesnerioides but are cross incompatible with cultivated cowpea. Some lines among the cross compatible wild relative V. unguiculata ssp. dekindtiana were found to be resistant to aphid in the seedling stage, while others showed good levels of drought and heat tolerance. Molecular markers are being generated to identify quantitative trait loci (QTL) with effects on some desirable attributes in cowpea. Modern breeding tools, including transgenics, can be applied for the improvement of cowpea, bypassing the natural barriers of traditional breeding. Transgenic cowpea with Bt gene cry1Ab showing resistance to M. vitrata has been released in Nigeria. Genome editing, a powerful emerging tool, can also be used for developing improved cowpea varieties with durable resistance to pests and diseases.